PRESCISO URGENTE QUE ALGUEM ME AJUDE!!!!!!!!
Se A = 3x + 4y + 5, B = 2x + 2y - 3 e C = +4x – y + 4, então A – B + C é igual a: * + x + y + 12 +x + 2y + 12 + 4x + y + 12 + 5x + y + 12
Soluções para a tarefa
Respondido por
0
Resposta:
x = -7
Explicação passo-a-passo:
3x + 4y + 5 - 2x + 2y - 3 + 4x – y + 4 = 5x + 5y + 6
5x + 5y + 6 = x + y + 12 +x + 2y + 12 + 4x + y + 12 + 5x + y + 12
5x + 5y + 6 = 11x + 5y + 48
5x + 6 = 11x + 48
-6x = 42
x = -7
Perguntas interessantes
Matemática,
9 meses atrás
História,
9 meses atrás
História,
9 meses atrás
Português,
1 ano atrás
Filosofia,
1 ano atrás
Informática,
1 ano atrás